Vanguard projects as relay races: A historical case study on the building of Eurocan pulp and paper mill, 1965–1970. Issue 5 (July 2021) - Laurila, Juha; Ahola, Tuomas
Highlights: We focus on interaction amongst actors involved in a vanguard project. We apply historical case study method on Enso's building of Eurocan paper mill, 1965–1970. We find that vanguard projects are characterised by a high degree of actor heterogeneity. We find that the centrality of actors tend to vary across the vanguard project life-cycle. We find that vanguard projects are particularly prone to external influences. Abstract: Previous research recognises the strategic role of vanguard projects in providing their initiators with avenues for entering new markets or gaining mastery over innovative technologies. This study makes a contribution to this research by focusing on the extent to which vanguard projects are under control and serve the interests of their principal initiators and the other actors involved. Simultaneously, the present study contributes to project management research by applying historical case study methodology on Eurocan, a vanguard project that a major Finnish forest industry firm Enso established in the mid-1960s to the wilderness of British Columbia, Canada. Our historical analysis encourages regarding vanguard projects as relay races in which several actors participate, largely in unanticipated ways. This is especially because the initiation of vanguard projects appears to be characterised by both the heterogeneity of the actors involved, a wide variety of actions taken by these actors to increase their centrality in the project organisation as well as abrupt changes among them and their relative importance over the project lifecycle. Together these characteristics make vanguard projects particularly prone to influence from external actors and events.